2017
DOI: 10.1007/s11219-017-9373-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of requests for user feedback on Quality of Experience

Abstract: Companies are interested in knowing how users experience and perceive their products. Quality of Experience (QoE) is a measurement that is used to assess the degree of delight or annoyance in experiencing a software product. To assess QoE, we have used a feedback tool integrated into a software product to ask users about their QoE ratings and to obtain information about their rationales for good or bad QoEs. It is known that requests for feedback may disturb users; however, little is known about the subjective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…The users' involvement is mostly limited to the opportunity to provide feedback in predefined testing situations and concepts that were created by others [Sanders and Stappers, 2008]. Fotrousi, Fricker and Fiedler [2017] showed that users must be able to provide feedback in a way that is intuitive and desired by the user, especially in regard to the timing and content parameters of a feedback form. Special mobile feedback apps [Seyff, Ollmann and Bortenschlager, 2014], application distribution platforms (Google Play Store, App Store) [Pagano and Maalej, 2013], email, and citizen science platform forums [Scanlon, Woods and Clow, 2014;Woods, McLeod and Ansine, 2015] have proven to be useful sources for user feedback, which is characterised by on-site use.…”
Section: User Feedback In User-centred Designmentioning
confidence: 99%
“…The users' involvement is mostly limited to the opportunity to provide feedback in predefined testing situations and concepts that were created by others [Sanders and Stappers, 2008]. Fotrousi, Fricker and Fiedler [2017] showed that users must be able to provide feedback in a way that is intuitive and desired by the user, especially in regard to the timing and content parameters of a feedback form. Special mobile feedback apps [Seyff, Ollmann and Bortenschlager, 2014], application distribution platforms (Google Play Store, App Store) [Pagano and Maalej, 2013], email, and citizen science platform forums [Scanlon, Woods and Clow, 2014;Woods, McLeod and Ansine, 2015] have proven to be useful sources for user feedback, which is characterised by on-site use.…”
Section: User Feedback In User-centred Designmentioning
confidence: 99%
“…The functionality of a software product, delay in data transmission, and a content of a media are examples of the system factors. Most of the system factors are relevant to the technical quality of the product or service (Fotrousi, Fricker, Fiedler, 2017). System factors, according Fotrousi et al (2017), include the properties and characteristics of a system that reflect its technical quality, such as its performance, usability, and reliability (ISO/IEC 25010).…”
Section: Monographic Analysis Of the Problem Areamentioning
confidence: 99%
“…The software users could be characterized by rather stable demographic, physical, and mental attributes, as well as more volatile attributes, such as temporary emotional attitudes (Fotrousi, Fricker, Fiedler, 2017). According Kujala and Miron-Shatz (2013) the human factors could be exemplified by mentioning needs, motivations, expectations, and moods of end-users.…”
Section: Monographic Analysis Of the Problem Areamentioning
confidence: 99%
“…We aimed at understanding the problems of the developed prototype systems and identify opportunities to evolve them to increase value creation and quality-of-experience. The monitoring data turned out to be difficult to interpret, and the user feedback requests were disturbing for users [6] or lacked enough information about the context to which the feedback applied.…”
Section: Introductionmentioning
confidence: 99%